STUDI PEMIKIRAN KH. SALIM MA’RUF TENTANG ‘ÂRIYAH, RAHN, WADÎ’AH DALAM RISÂLAH MU’ÂMALÂT: STUDY OF THOUGHT KH. SALIM MA'RUF ABOUT 'ÂRIYAH, RAHN, WADÎ'AH IN THE RISÂLAH MU'ÂMALÂT - Sauqi, Muhammad; Ulfah, Mariya; Masdian, Masdian (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This research is motivated by the thoughts of K.H. Salim Ma'ruf on Islamic economics in the treatise mu'âmalât which discusses 'âriyah, rahn, wadî'ah. However, he did not mention the arguments and 'illat law, this is of course different from most of the scholars who state the arguments and 'illat law for their opinion. In fact, the inclusion of the arguments and 'illat law is important to know the clarity of the law. What's more, in his treatise there is an opinion that is different from the opinion of other Shafi'iyyah scholars, whereas he does not explain the legal basis or his 'illat. Therefore the focus of this research is What are the arguments and 'illat underlying the thoughts of K. H. Salim Ma'ruf 'âriah, wadî'ah, rahn in the Risâlah Mu'âmalât and How is the istinbath method used by K. H. Salim Ma'ruf 'ariah, wadî'ah, rahn in the treatise mu'âmalât. The method used according to its type is literature review and is classified as legal philosophy research because the focus of study in this research is legal thinking. The results of the study show that K. H. Salim Ma'ruf's Islamic economic thought regarding âriyah, rahn, wadî'ah in the Risâlah Mu'âmalât is based on the Koran and hadith, besides that he also cited several fiqh books which were used as the basis, namely,